Analysis of Tax Incentives Policy for Tourism Sector in Indonesia as Economic Stimulus during the Covid-19 Outbreak - Made Laksmi Sena Hartini; Kadek Apriada (Advances in Global Economics and Business Journal, 2020)
Tourism sector is one of the sectors significantly affected by Covid-19 pandemic. The government has provided various stimulus in fiscal and non-fiscal, one of them is tax incentives for tourism sector. This study used explorative and descriptive approach, and a qualitative method with exploratory and descriptive approach. The study underlined several tax incentives to increase the people's purchasing power and productivity in the tourism sector, thus socializing any tax regulation is necessary to avoid problems in the application.